2011
DOI: 10.1007/s00395-011-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Unequal allelic expression of wild-type and mutated β-myosin in familial hypertrophic cardiomyopathy

Abstract: Familial hypertrophic cardiomyopathy (FHC) is an autosomal dominant disease, which in about 30% of the patients is caused by missense mutations in one allele of the β-myosin heavy chain (β-MHC) gene (MYH7). To address potential molecular mechanisms underlying the family-specific prognosis, we determined the relative expression of mutant versus wild-type MYH7-mRNA. We found a hitherto unknown mutation-dependent unequal expression of mutant to wild-type MYH7-mRNA, which is paralleled by similar unequal expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
78
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 45 publications
(85 reference statements)
14
78
0
Order By: Relevance
“…Indeed, the LVWT in 403i-treated MHC 403/+ mice, with or without CsA, was comparable to that in wild-type mice. Based on these findings and evidence for unequal expression of mutated and wildtype MYH7 mRNAs in human HCM hearts (23), we suggest that variable penetrance and severity of HCM may reflect, at least in part, the proportion of wild-type and mutant transcripts and proteins.…”
mentioning
confidence: 75%
“…Indeed, the LVWT in 403i-treated MHC 403/+ mice, with or without CsA, was comparable to that in wild-type mice. Based on these findings and evidence for unequal expression of mutated and wildtype MYH7 mRNAs in human HCM hearts (23), we suggest that variable penetrance and severity of HCM may reflect, at least in part, the proportion of wild-type and mutant transcripts and proteins.…”
mentioning
confidence: 75%
“…A previous study reported variability in the fraction of mutant mRNA for 5 MYH7 variants, 39 but was limited by use of skeletal muscle biopsies, analysis of benign variants, and less sensitive methods than the primer extension technique. While it is possible that differences could be due to specific mutations analyzed, we think this is a less plausible explanation given that non-PTC containing transcripts are not substrates for NMD, and should be intrinsically stable.…”
Section: Discussionmentioning
confidence: 99%
“…39, 40 An important distinction from previously published methodologies is the recognition of missed cleavages and post-translational modifications which was critical for accurate absolute and relative quantification of wild-type and mutant peptides by AQUA. For one mutation, MYBPC3 Arg495Gln, the mutant peptide was similarly ~2-fold more abundant than wild-type in 2 samples from unrelated HCM patients, implying that preferential expression or stability of the mutant protein is an inherent property of a particular mutant protein rather than a function of other modifying factors.…”
Section: Discussionmentioning
confidence: 99%
“…V606 lies in the 50 KDa portion of the myosin S1 head, where it contributes to the actin-binding site 9 . R453C has been associated with more severe human HCM and is located within the γ-phosphate sensing domain of the myosin ATPase 10 . When engineered in vitro into human β myosin, the R453C mutation has reduced actin-activated ATPase and directs slower in vitro sliding of actin filaments 11 .…”
mentioning
confidence: 99%
“…However, altered actin binding plus reduced ATPase evoked significantly more hypertrophy, suggesting a disease model wherein the cardiac sarcomeres contain a mixture of myosin heads, some with different actin binding and others with reduced ATPase. These mixed mutations may or may not reflect a situation where each allele produces half the total MHC protein, as V606M and R719W may not be expressed at equal levels to the normal allele 10 . It is also possible that some mutations may alter mRNA stability and splicing, provoking reduced expression of the mutant protein relative to normal MHC, thereby leading to less hypertrophy.…”
mentioning
confidence: 99%